Adding sorbitan sesquioleate to the European baseline series: Necessary, reasonable, or unavoidable?. (27th June 2019) - de Groot, Anton; Gilissen, Liesbeth; Geier, Johannes; Orton, David; Goossens, An
Abstract: Positive reactions to fragrance mix I (FM I) are frequent in consecutively patch tested patients suspected of having allergic contact dermatitis. However, the FM I test preparations contain 5% of the emulsifier sorbitan sesquioleate (SSO), and it is well known that SSO can cause contact allergic reactions in its own right. Indeed, the available data show that some patients with contact allergy to SSO react to FM I but are not allergic to fragrances. When SSO is not tested, this situation may go unnoticed, a wrong diagnosis of fragrance allergy may be given to the patient, and unjustified advice to avoid fragrances and fragranced products will be given in such cases. To avoid such suboptimal patient care, we postulate that testing with SSO in all patch tested individuals is mandatory. As it is well known that only a minority of FM I‐reactive patients will undergo a breakdown test with the ingredients and SSO, testing with SSO in all patients can only be achieved by adding it to the European baseline series. Not testing with SSO may also result in misinterpretation of patch test reactions to Myroxylon pereirae resin and 2‐hydroxyethyl methacrylate in the baseline series, as both (may) contain SSO, and, for the same reason, of reactions to several other hapten test materials.